The assistance of MSMEs in Halal Licensing Certification to Improve Consumer Trust and Health in Cimahi City - Harun Heri Trismiyanto; Ali Taifan; Iing Nurdin; Moch. Zaelani; Yudi Sugiarto (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
The purpose of this Service Activity is to provide knowledge, understanding and assistance about the importance of halal certification and licensing for Micro, Small and Medium Enterprises (MSMEs), especially in Cimahi City. The method used in this Community Service is to conduct face-to-face training (offline) by taking into account the Health protocol. This training activity is not only providing knowledge but also providing assistance for offline registration of halal product guarantee certification for MSME actors engaged in the food sector. The purpose of this training is to provide knowledge, understanding, the importance of applying for halal certification, and procedures for submitting halal certification offline. With this training and assistance in the halal certification process, the problem of how to apply for a halal certificate that is considered complicated can be resolved and can be an example for other MSME actors around the City of Cimahi.